Secure Attachment (Kelekatan Aman) Ibu dan Anak dengan Perkembangan Sosial Emosional Pada Anak - Arianda, Vinny; Salim, Irma Kusuma; Ruzain, Raihanatu Binqolbi (Journal of Islamic and Contemporary Psychology, 2022)
This study was conducted to determine whether or not there is a relationship between secure attachment between mother and child and social emotional development. One of the factors that play a major role in the social and emotional development of children is secure attachment. This study uses a correlational quantitative method with a side technique, namely purposive sample with the number of subjects as many as 97 students' guardians (especially mothers) at RA Aisyah IT Pekanbaru. The results of the correlation test between the secure attachment variable and social emotional development using Pearson product moment analysis showed a probability number (sig 2-tailed) 0.001 (p <0.005) which indicated that the two variables had a significant positive relationship with a correlation value of 0.332. This means that the higher the secure attachment, the higher the social-emotional development, and conversely, the lower the secure attachment, the lower the social- emotional development.